The Digital Applications of “Agriculture 4.0”: Strategic Opportunity for the Development of the Italian Citrus Chain - Alessandro Scuderi; Giovanni La Via; Giuseppe Timpanaro; Luisa Sturiale (Agriculture, 2022)
Contemporary agriculture is increasingly oriented toward the synergistic adoption of technologies such as the Internet of Things, Internet of Farming, big data analytics, and blockchain to combine resource protection and economic, social, and environmental sustainability. In Italy, the market growth potential of “Agriculture 4.0” and “Farming 4.0” solutions is very high, but the adoption of the related technological innovations is still low. Italian companies are increasingly aware of the opportunities offered by the 4.0 paradigm, but there are still cultural and technological limits to the full development of the phenomenon. This research aims to contribute to knowledge that will improve the propensity of agricultural operators to adopt the digital solutions of “Agriculture 4.0” by demonstrating its potential, along with its limits. To this end, an integrated methodological approach was adopted, built with focus groups and multicriteria analysis, to define and assess the possible future scenarios resulting from the implementation of digital transformation. The results show an increased focus on solutions that allow the integration of new tools to support those already used in the business organization and at a sustainable cost. To enable the development of “Agriculture 4.0”, we propose that it is necessary to invest in training operators in the supply chain, and above all, raising awareness among farmers, who it is essential fully appreciate the potential benefits of the 4.0 revolution.